Fruit tree leaves as unconventional and valuable source of chlorophyll and carotenoid compounds determined by liquid chromatography-photodiode-quadrupole/time of flight-electrospray ionization-mass spectrometry (LC-PDA-qTof-ESI-MS). (1st July 2021) - Wojdyło, Aneta; Nowicka, Paulina; Tkacz, Karolina; Turkiewicz, Igor Piotr
Graphical abstract: Highlights: 16 chlorophylls and 7 carotenoids were identified by LC-MSqTof in fruit tree leaves. Fruit tree leaves are promising sources of isoprenoids. Fruit tree leaves are richer in carotenoids than chlorophylls. Chlorophylls a and b dominate compounds in fruit tree leaves. Abstract: This study focused on the identification (by LC-PDA-qTof-ESI-MS) and quantification (by UPLC-PDA) of isoprenoids of the fruit tree leaves (FTL) of commonly consumed fruits: apple, pears, quince, apricot, peach, plums, sweet and sour cherry. The FTL were collected at 2 time points: after tree blooming and after fruit collection. In FTL 7 carotenoids and 16 chlorophylls were identified, but the number of labeled chlorophyll compounds depended on the species. FTL of apple, sour cherry and apricot were identified as the best sources of chlorophylls (mean 404.8, 388.7 and 364.5 mg/100 g dw, respectively) and sweet and sour cherry leaves as the best sources of carotenoids (831.4 and 1162.0 mg/100 g dw, respectively). A lower content of chlorophylls and carotenoids, but not significantly, was detected in leaves after autumn collection of fruits compared to leaves collected after blooming. Fruit tree leaves are good material for isolation of chlorophylls and carotenoids for application in cosmetics, pharmaceuticals or in the food industry, e.g. production of beverages or puree.